Pengaruh Profitabilitas dan Sales Growth Terhadap Tax Avoidance (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar di BEI Tahun 2019-2021) - Dinantia, Salsabila; Soedarsa, Herry Goenawan (Jurnal EMT KITA, 2023)
This study aims to determine the effect of profitability and sales growth on tax avoidance of manufacturing companies in the consumer goods industry sector which are listed on the IDX in 2019 - 2021. There are several factors that influence a company in carrying out its tax obligations, including profitability, leverage, and corporate governance. This research method uses quantitative methods. The samples involved were 57 companies within 3 years. The testing procedure used is purposive sampling. Data analysis for this study used multiple linear regression tests. The results showed that profitability and sales growth had a positive and significant effect on tax avoidance.